Тектонічна обумовленість річкової мережі Кременецьких гір - Бермес, А. Р. (Київський національний університет імені Тараса Шевченка, 2018)
Схарактеризовано особливості геоморфологічної будови Кременецьких гір. Проведено структурний аналіз ерозійної мережі Кременецьких гір, виділено ерозійні тальвеги на основі топографічних карт масштабу 1:25000, проведено головний вододіл між основними річковими басейнами (річок Ікви та Вілії), окреслено території цих басейнів. Виділені тальвеги ерозійних водотоків поділено за методикою Страллера та наведено результати підрахунку коефіцієнту біфуркації (розгалуженості) ерозійної мережі за методикою Хортона. Побудовано та проаналізовано рози-діаграми тальвегів ерозійних водотоків за рівновеликими квадратами, зі стороною в 10 км. Наведено результати орієнтування ерозійних тальвегів, лінеаментної мережі та тріщинуватості порід на території Кременецьких гір, охарактеризовано головні і другорядні напрями. Підтверджено зв'язок річкової мережі та тектонічних особливостей в межах Кременецьких гір. Також, проаналізовано отримані значення орієнтування із сусідніми ділянками Подільської та Волинської височин.

The features of the geomorphological structure of Kremenets mountains are described. Structural analysis of the erosion network of the Kremenets Mountains, erosion network are selected on the basis of topographic maps of scale 1: 25000, the main watershed between the main basins (rivers Ikva and Vilia) has been carried out, the territories of these basins have been identified. Particular stream order erosion network are divided according to the method of Streller and the results of calculating the coefficient of bifurcation to the method of Horton (branching of the erosive network). Rose diagrams of stream order erosion network in equal squares, with a side of 10 km are made and analyzed. Results of orientation of erosion network, lineaments network and fracture of the rocks are presented, main and secondary directions are described. The connection of the river network and tectonic features within the Kremenets mountains has been confirmed. Also, the received orientation values are analyzed with neighboring areas of the Podilsk and Volyn uplands. As a result of the study presented in this publication, it was established that the direction of the erosion network, the lineaments system and the fracture of the rocks are interconnected, their directions generally coincide, which may indicate their genetic link. The structure of the erosion network of the Kremenets mountains accord to the structure-denudation’s nature of the relief. Together with the pronounced asymmetry of the upland, this factor determines the characteristic location of erosion network and their distribution in the studied area. Using the constructed rose’s diagrams, the regularities of orientation of erosion network and the presence of several zones with dominant directions were revealed. The discrepancy between the boundaries of these zones with the most pronounced zones of discontinuity violations allows us to assume that neotectonic movements within the studied area were mainly vertical. In this case, the main directions of cracking of rocks, which predetermines the formation of erosion forms, formed in more ancient geological period.
Tectonic conditionality erosion network of the Kremenets mountains
Keywords: Кременецькі гори; ерозійна мережа; порядок водотоків; Північно - Подільський уступ; рози-діаграми; лінеаменти; тріщинуватість; Kremenets mountains; drainage network; stream order; North-Podilskyj ledges; roses diagrams; lineaments; fracture of the rocks